Exchange rate dynamics in a target zone - a heterogeneous expectations approach - Bauer, Christian 1973- (Dt. Bundesbank, 2007)
We present a simple behavioral model with chartists and fundamentalists and analyze their trading behavior in a floating regime and in a target zone regime. Regarding the floating regime the model replicates the well-known stylized facts like excessive volatility, fat tails,volatility clustering and the exchange rate disconnect. When introducing a credible target zone the exchange rate remains for a considerably long period in the center of the bandalbeit the fundamental exchange rate does not exhibit mean reversion tendencies. The resulting hump-shaped distribution of the exchange rate greatly reduces the frequency of central bank intervention. The introduction of a target zone regime significantly reduces exchange rate volatility by decreasing speculative activity in the FX market.